Simbol Dalam Film Wall-E Sutradara Andrew Stanton - Tabdilah Marjan Wafda (Universitas Palangka Raya, 2025)
This study analyzes the use of symbols in the animated film Wall-E, directed by Andrew Stanton, which conveys environmental and social issues through a semiotic lens. The research applies a descriptive qualitative method, focusing on the interpretation of signs and meanings embedded within the film’s visual elements and narrative structure. The aim is to explore how symbolic representations contribute to the film’s critique of human behavior and modern lifestyles. The findings identify several key symbols used throughout the film. The barren, deserted Earth serves as a metaphor for environmental destruction caused by human greed and overconsumption. Wall-E, the main character, symbolizes resilience and hope amidst ecological collapse. A small green plant becomes a central symbol of renewal and the possibility of life returning to Earth. The spaceship Axiom represents a society dominated by extreme consumerism, where humans have become passive, dependent, and physically detached from nature. Additionally, the depiction of human interactions—or the lack thereof—illustrates the theme of social alienation driven by overreliance on technology. These symbols collectively function as a powerful critique of unsustainable living patterns, warning audiences of the consequences of neglecting environmental responsibility. Furthermore, the film emphasizes the need for balance between technological advancement and ecological awareness. In conclusion, this research highlights the effectiveness of animated films like Wall-E in delivering social and environmental messages. It suggests that cinema can be a potent medium for raising awareness, fostering critical thinking, and educating audiences about the importance of sustainability and human connection in the face of modern challenges.